Mozambique Economic Update, October 2018 : Shifting to More Inclusive Growth - World Bank (World Bank, Washington, DC, 2018)
Mozambique is beginning to emerge from a period of elevated macroeconomic volatility two years after hidden debt revelations triggered a significant economic downturn, but with a reduced capacity for growth. Having averaged near 8 percent between 2005 and 2015, GDP growth dropped to 3.7 in 2017 and is projected to fall further to 3.3 percent in 2018 as slower growth in coal production is expected to offset any modest upturn in manufacturing and services. Fiscal consolidation is making progress, but debt levels continue to be a concern. In an analysis of the structure and drivers of Mozambique's growth over the past two decades, the report notes that progress in reducing poverty levels have come as the expense of rising inequality. Therefore, shifting the growth model to broaden the drivers of growth and to raise productivity in sectors with the highest employment potential is a primary challenge facing Mozambique's policy makers today.